Global distribution of two fungal pathogens threatening endangered sea turtles. - Jullie M Sarmiento-Ramírez; Elena Abella-Pérez; Andrea D Phillott; Jolene Sim; Pieter van West; María P Martín; Adolfo Marco; Javier Diéguez-Uribeondo (PLoS ONE)
Nascent fungal infections are currently considered as one of the main threats for biodiversity and ecosystem health, and have driven several animal species into critical risk of extinction. Sea turtles are one of the most endangered groups of animals and only seven species have survived to date. Here, we described two pathogenic species, i.e., Fusarium falciforme and Fusarium keratoplasticum, that are globally distributed in major turtle nesting areas for six sea turtle species and that are implicated in low hatch success. These two fungi possess key biological features that are similar to emerging pathogens leading to host extinction, e.g., high virulence, and a broad host range style of life. Their optimal growth temperature overlap with the optimal incubation temperature for eggs, and they are able to kill up to 90% of the embryos. Environmental forcing, e.g., tidal inundation and clay/silt content of nests, were correlated to disease development. Thus, these Fusarium species constitute a major threat to sea turtle nests, especially to those experiencing environmental stressors. These findings have serious implications for the survival of endangered sea turtle populations and the success of conservation programs worldwide.